Pemilihan Karakter Agronomi untuk Seleksi pada Galur-galur Padi Dihaploid Hasil Kultur Antera - Akhmadi, Gerland; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Wirnas, dan Desta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Anther culture technique is able to accelerate plant breeding activities. The objectives of this research was to determine the agronomic traits that could be used for selection of the dihaploid rice line population through the calculation of heritability, genotypic correlation, path analysis and selecting dihaploid rice lines. The plant material used was 65 dihaploid rice lines DH 1 of F1 anther culture plants and Ciherang and Inpari 13 as check varieties. Agronomic characters that could be used as selection character are generative plant height, number of filled grain per panicle, the total number of grains per panicle, weight of 1,000 grains, and grain per hill. Twenty three dihaploid lines were selected based good agronomic characters with criteria generative plant height between 80-120 cm, number of filled grains per panicle > 100, number of grains per panicle > 120, weight of 1,000 grains > 20 g, and grain per hill > 25 g.Keywords: anther culture, heritability, agronomic characters